High-throughput approach for estimation of intrinsic barriers in FCC structures for alloy design. (November 2021) - Vamsi, K.V.; Charpagne, M.A.; Pollock, T.M.
Abstract: Generalized stacking/planar fault energy (GSFE/GPFE) curves provide the intrinsic energy barriers (IEBs) for plastic deformation in FCC structures. In this study, we propose a new approach for estimation of these IEBs. A strong correlation between the unstable fault energies and shear modulus on the {111} planes is shown for a large set of pure FCC metals. Interestingly, data from the literature also obeys this correlation for a variety of FCC solid solutions. High-throughput estimation of the IEBs combining these correlations with a diffuse multi-layer fault model for stable fault energies is demonstrated for pure FCC metals and FCC (Ni0.5 Co0.5 )1-x Rux (x=0 to 0.5). Additionally, other important descriptors for alloy design, including critical stresses for slip and twinning, were estimated. This new approach opens avenues for the high-throughput design of multi-principal element alloys (MPEAs) based on the propensity for twinning and deformation pathways. Graphical Abstract: Image, graphical abstract